THE INFLUENCE OF PROMOTION, INNOVATION, PRICE, ON RE-PURCHASES AT MADYA BURUNG STORES WITH LOYALTY AS A MEDIATION VARIABLES - Shella Febiola Siswanto; I Made Bayu Dirgantara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to examine the effects of promotion, innovation, and price on repeat purchase in intermediate bird shops with loyalty as a mediating variable. The research problem is how to increase customer loyalty toward repurchase intention in middle bird shops. The variable used in this study is promotion, innovation, price as the independent variable, loyalty as variable intervening and repeat purchase as the dependent variable. The sampling method used on this research is purposive sampling technique. Sample collected from 100 respondents of customer in Madya Bird Store. Technique of data collection conducted by survey through interviews and questionnaires. Data analysis was performed by descriptive analysis method and the method of Partial Least Square (PLS). The result showed that customer on average make repurchase in toko madya Burung more than twice. The result of data analysis using the PLS indicates that there is a positive and significant through promotion, innovatin, and price in the repeat purchase. Based on the research results, repeat purchase can be increased through consumer loyalty. Keywords: promotion, innovation, price, repeat purchase, loyalty.